HUBUNGAN KEMAMPUAN MEMBACA PEMAHAMAN DAN MOTIVASI SISWA DENGAN HASIL BELAJAR IPS KELAS IV (Universitas Negeri Semarang, 2018)
This study aims to examine the relationship between students' ability to read comprehension and motivation with social learning learning outcomes of fourth grade students of SDN cluster Nyi Ageng Serang, Semarang City. This study uses a correlation method with a quantitative approach. Samples of 103 students of class IV taken using saturated sampling. Data collection techniques using tests, questionnaires and documentation. Data analysis techniques with descriptive statistics, correlation analysis, and regression analysis. The results showed a positive relationship between reading comprehension ability and learning motivation with social learning learning outcomes of fourth grade students of SDN cluster Nyi Ageng Serang Semarang City. The results showed that: (1) there was a relationship between reading comprehension and learning outcomes with a correlation coefficient of 0.827; (2) there is correlation between student motivation with learning result with correlation coefficient 0,710; (3) there is a relationship between reading and motivation with learning outcomes with a correlation coefficient of 0.817; (4) the coefficient of determination (R2) reads understanding and learning motivation is 0.717 so that it gives a positive impact together by 71.1% on social learning learning outcomes while 28.3% is influenced by other variables. it can be concluded that there is a relationship between reading comprehension and motivation together with IPS learning outcomes. Teachers should motivate students in learning and improve the ability to read comprehension so that learning outcomes can increase. From the results of the study it can be concluded that there is a positive relationship between the ability to read students' understanding and motivation with the social learning learning outcomes of grade IV SDN Gugus Nyi Ageng Serang Semarang City.